2022
DOI: 10.3390/su14138066
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and Academic Dropout in Ecuadorian University Students during COVID-19

Abstract: The pandemic caused by COVID-19 has had a global impact that has affected all areas of people’s lives. However, people have different capacities to adapt and cope with the adversities and traumatic events that may have occurred during the pandemic with different levels of resilience. One collective affected by this global crisis was university students, who had to face an unprecedented academic situation, resulting in some abandoning their studies. This study aims to analyse whether the resilience of the stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
1
8
0
5
Order By: Relevance
“…These findings are aligned with work from South America which found that 38% of students reported economic distress (related to food insecurity risk) as a key motive to dropout early in the pandemic, while dropout motives related to mental distress increased over time reaching 40% in 2021 ( 1 ). There is also evidence linking poor family resources as well as an inability to cope with low resilience, and ultimately heighted risk for dropout, further corroborating the findings from the current study ( 51 ).…”
Section: Discussionsupporting
confidence: 88%
“…These findings are aligned with work from South America which found that 38% of students reported economic distress (related to food insecurity risk) as a key motive to dropout early in the pandemic, while dropout motives related to mental distress increased over time reaching 40% in 2021 ( 1 ). There is also evidence linking poor family resources as well as an inability to cope with low resilience, and ultimately heighted risk for dropout, further corroborating the findings from the current study ( 51 ).…”
Section: Discussionsupporting
confidence: 88%
“…In such an environment, self-organization and communication skills of the students become increasingly important [14]. Also, understanding the logical structure of physics requires resilience which many students may have lacked in the stressful environment created by the pandemic [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the engineering persistence issue has been exacerbated further by the COVID-19 pandemic since early 2020 due to the impact of structural barriers and inequities. For instance, the pandemic abruptly affected students' decision to leave their engineering major, which aggravated students' interpersonal problems, family resources, sociocultural resources, and coping strategies (Kang, 2021;Pertegal-Felices et al, 2022). Furthermore, studies have documented several issues disrupted the online engineering education in which half of the students experienced lack of engagement in online class and difficulties in maintaining their focus during online sessions (Alexa et al, 2022;Asgari et al, 2021;Ghasem & Ghannam, 2021).…”
Section: Introductionmentioning
confidence: 99%